1995
DOI: 10.1111/j.1468-232x.1995.tb00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring, Grievances, and Plant Performance

Abstract: This study develops the theory and an in‐depth longitudinal study of the role of residual grievance activity as a suggested proxy for managerial monitoring within the context of manufacturing production. In the empirical section, we test the theory and practice within the firm for the optimal level of monitoring/grievances in an establishment with monthly data over a ten‐year period. We find that production‐related residual grievances could indicate increased managerial monitoring of a kind that has a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
0
15
0
3
Order By: Relevance
“…The size of the productivity and cost effects reported in the aforementioned studies, however, seem too large to be fully accounted for by such a displacement effect. Moreover, a study by Kleiner, Nickelsburg, & Pilarski (1995) of grievance procedures and firm performance in a large unionized aerospace company found that the lowest levels of unit labor costs were associated with a "moderate" level of grievance activity.…”
Section: Economics Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The size of the productivity and cost effects reported in the aforementioned studies, however, seem too large to be fully accounted for by such a displacement effect. Moreover, a study by Kleiner, Nickelsburg, & Pilarski (1995) of grievance procedures and firm performance in a large unionized aerospace company found that the lowest levels of unit labor costs were associated with a "moderate" level of grievance activity.…”
Section: Economics Researchmentioning
confidence: 99%
“…Using an agency theory framework, Kleiner, Nickelsburg, & Pilarski (1995) hypothesized that management monitoring of employees would be positively related to grievance filing. The researchers were unable to develop a direct quantitative measure of such monitoring.…”
Section: Economics Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Un certain nombre d'études ont été réalisées en se basant sur divers indicateurs reliés au climat pour évaluer l'impact des RI sur la performance. Les griefs, les mesures disciplinaires, le roulement du personnel, l'absentéisme et les grèves sont quelques-uns des indicateurs employés (Katz, Kochan et Gobeille 1983 ;Katz, Kochan et Weber 1985 ;Norsworthy et Zabala 1985 ;Mefford 1986 ;Ichniowski 1986 ;CutcherGershenfeld 1991 ;Kleiner, Nickelsburg et Pilarski 1995). De façon géné-rale, ces études concluent qu'un bon climat favorise la performance et, qu'à l'inverse, un mauvais climat la détériore peu importe la dimension étudiée.…”
Section: Impact Du Climat Riunclassified
“…Ces coûts d'implantation peuvent constituer un frein à la diffusion des pratiques dites « innovatrices » (Pil et MacDuffie 1996) qui, selon d'autres (Cappelli et Neumark 2001), sont susceptibles d'accroître les coûts de main-d'oeuvre, en raison des qualifications plus éle-vées de la main-d'oeuvre (Bailey, Berg et Sandy 2001). D'un autre côté, d'autres études (Kleiner, Nickelsburg et Pilarski 1995 ;Cutcher-Gershenfeld 1991) montrent que certaines pratiques RI diminuent les coûts, notamment en permettant une réallocation des ressources. Pour réconcilier ces tendances apparemment contradictoires, il faut poser que les pratiques sont susceptibles d'augmenter les coûts de production à court terme mais que cet effet diminue avec le temps.…”
Section: Hypothèsesunclassified